Synergistic metal halide perovskite@metal-organic framework hybrids for photocatalytic CO2 reduction - Sharma, Saandra; Jacob, Noah; Grandhi, G Krishnamurthy; Choudhary, Mahendra B; Ippili, Swathi; Hathwar, Venkatesha R; Vivo, Paola; Lo, Rabindranath; Motapothula, M; Jayaramulu, Kolleboyina (iScience, 2024)
The photocatalytic reduction of carbon dioxide (CO2) into multi-electron carbon products remains challenging due to the inherent stability of CO2 and slow multi-electron transfer kinetics. Here in, we synthesized a hybrid material, cesium copper halide (Cs3Cu2I5) intercalated onto two-dimensional (2D) cobalt-based zeolite framework (ZIF-9-III) nanosheets (denoted as Cs3Cu2I5@ZIF-1) through a simple mechanochemical grinding. The synergy in the hybrid effectively reduces CO2 to carbon monoxide (CO) at 110 μmol/g/h and methane at 5 μmol/g/h with high selectivity, suppressing hydrogen evolution. Further, we have investigated additional Cs3Cu2I5@ZIF hybrids with varying ZIF-9-III amounts, confirming their selective CO2 reduction to methane over hydrogen. Density functional theory (DFT) calculations reveal a non-covalent interaction between Cs3Cu2I5 and ZIF-9-III, with electron transfer suggesting potential for improved photocatalysis.
Keywords: Catalysis; Chemistry